PROMOSI UNIVERSITAS SWASTA DALAM MENARIK MINAT MAHASISWA BARU - Nurhayati, Isna; Mulyadi, Andi (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to determine the extent to which the University of Muhammadiyah Sukabumi (UMMI)Â  promote academic programs into the middle of society, so that people knew and eventually took an interest to study at UMMI. The method applied is qualitative research method with a case study approach (case study), and data collection techniques by means of literature studies, interviews and questionnaires distribution. The study population was a group of UMMI students Academic Year 2014/2015 and 2015/2016, while the random technique applied was purposive sample. The result shows that the promotional efforts undertaken by UPT HPPMB against students Senior High Schools/Vocational High Schools/Madrasah Aliah High Schools have done optimally because it has managed to get the students with higher numbers when comparing to the number of students in the two previous years.